Intake Analysis On Four-Stroke Engine Using CFD - R. A., Bakar; A. M., Mohd Shafie; Musthafah, M. T.; M. S., Ali (2014)
Flow pattern is vital to ensure that the engine can produce high performance with the presence of swirl and tumble inside the cylinder. In this paper, the simulation of air is simulated in the software to predict the flow pattern using the steady state pressure based solver at two different planes in the engine domain. The domain used for the simulation is based on the actual engine parameters. Using the commercial CFD solver ANSYS FLUENT, the CFD simulation is run under five different piston positions and seven different engine speeds. Note that in this simulation, only intake strokes are simulated. The results show the velocity of the flow is high during the sweep as the intake stroke takes place. This situation is believed to produce more swirl and tumble during the compression hence enhancing the burning rate in entire region of the clearance volume.